2006
DOI: 10.1007/s11095-006-0205-x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Fixed Dosing of Pertuzumab in Cancer Patients Based on Population Pharmacokinetic Analysis

Abstract: A population PK model was developed for pertuzumab, the first monoclonal IgG1 antibody in a new class of agents known as HER dimerization inhibitors. In addition, our analyses demonstrate the feasibility of administering pertuzumab using a fixed dose in women with ovarian and breast cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
78
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 19 publications
13
78
0
Order By: Relevance
“…This indicates that CL seems to remain stable independently of the patient's weight. A similar conclusion was drawn by Ng et al (2006) who observed that weight and body surface area were significant covariates, but had a weak impact on patient sample concentrations. Therefore, one could consider recommending a fixed-dose instead of a weight-based dosing regimen for HuHMFG1.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This indicates that CL seems to remain stable independently of the patient's weight. A similar conclusion was drawn by Ng et al (2006) who observed that weight and body surface area were significant covariates, but had a weak impact on patient sample concentrations. Therefore, one could consider recommending a fixed-dose instead of a weight-based dosing regimen for HuHMFG1.…”
Section: Discussionsupporting
confidence: 82%
“…Rarely does a combined linear and non-linear process describe the elimination of antibodies (Kuester et al, 2008). Values of the final parameters were similar to those reported for other antibodies, with regard to CL from the central compartment and Q, V1 and V2 (Kovarik et al, 2001;Bruno et al, 2005;Ng et al, 2006;Dartois et al, 2007;Mould et al, 2007;Kuester et al, 2008;Lu et al, 2008). This indicates that the HuHMFG1 antibody, similar to other therapeutic antibodies, is mainly distributed in the serum.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations